THE SIMPLE PRACTICUM KIT TO IMPROVE UNDERSTANDING OF THE STUDENT’S CONCEPT DYNAMIC ELECTRICITY - ALIYAH, ROFIATUL; HARIYONO, EKO (Inovasi Pendidikan Fisika, 2019)
The present study was conducted to describe an improved understanding of the students concept dynamic electricity. The simple practicum kit has unique characteristic in terms of being a 3-dimentional, simple, be equipped with symbols and safety device, interactive real laboratory that enables students to learn in cooperative class, and having been designed on the student?s of thinking level. The kind of research is true experimental with control group pretest posttest design. The samples of this study were XI IPA 2 as the experimental class with learning using by simple practicum kit and XI IPA 3 as the control class with conventional learning methods using by application. To determine 66 (n=32 experimental and n=34 control class) was using purposive sampling technique. The technique of data analysis was used as n gain based on the pretest and posttest. The results from the paired sample t-test indicated that the students who were learned using simple kit had significantly scores in terms of achievement than those taught by the traditional approach and it was also found n gain 0.57 in the medium category which indicated that the learning using simple kit was more successful in improving the understanding of the student?s concept dynamic electricity. Keywords: simple practicum kit, dynamic electricity, understanding of the concept